Arhgef5 Binds α-Dystrobrevin 1 and Regulates Neuromuscular Junction Integrity - Bernadzki, Krzysztof M.; Daszczuk, Patrycja; Rojek, Katarzyna O.; Pęziński, Marcin; Gawor, Marta; Pradhan, Bhola S.; de Cicco, Teresa; Bijata, Monika; Bijata, Krystian; Włodarczyk, Jakub; Prószyński, Tomasz J.; Niewiadomski, Paweł (Frontiers in Molecular Neuroscience, 2020)
The neuromuscular junctions (NMJs) connect muscle fibers with motor neurons and enable the coordinated contraction of skeletal muscles. The dystrophin-associated glycoprotein complex (DGC) is an essential component of the postsynaptic machinery of the NMJ and is important for the maintenance of NMJ structural integrity. To identify novel proteins that are important for NMJ organization, we performed a mass spectrometry-based screen for interactors of α-dystrobrevin 1, one of the components of the DGC. The guanidine nucleotide exchange factor Arhgef5 was found to be one of the α-dystrobrevin 1 binding partners that is recruited to Tyr-713 in a phospho-dependent manner. We show here that Arhgef5 localizes to the NMJ and that its genetic depletion in the muscle causes the fragmentation of the synapses in conditional knockout mice. Arhgef5 loss in vivo is associated with a reduction in the levels of active GTP-bound RhoA and Cdc42 GTPases, highlighting the importance of actin dynamics regulation for the maintenance of NMJ integrity.